Investigation of newly developed solid state fermenter on carboxymethyl cellulase production - Keong L.C.; Ibrahim D,; Omar I.C. (Malaysian Society for Microbiology, 2013)
Enzyme (cellulase) contributes 10% to overall cost in bioethanol production from lignocellulosic biomass. This means that the cost for bioethanol production will be reduced if cellulase can be produced using cheaper method. Compared with submerged fermentation, it is recognized that the cost for cellulase production using solid state fermentation (SSF) process is much cheaper. The present study aimed to optimize cellulase production via SSF process using agro-industrial residual as substrate. Methodology and result: Newly developed solid state bioreactor, FERMSOSTAT had been evaluated in cellulase production using local isolate Aspergillus niger USM AI 1 grown on sugarcane baggase and palm kernel cake as substrates at 1:1 (w/w) ratio. Under optimized SSF conditions of 0.5 kg substrate; 70% (w/w) moisture content; 30 °C; aeration at 4 L/h.g fermented substrate for 5 min and mixing at 0.5 rpm for 5 min, about 62.6 U/g of CMCase activity obtained. At the same time, comparative studies of the enzyme production under the same SSF conditions indicated that CMCase produced by Trichoderma reesei was about 9% lower compared with A. niger USM AI 1. Conclusion, significance and impact of study: It can be concluded that the performance of newly developed SSF fermenter is good since it can used to produce CMCase enzyme with reasonable good title (863% increased in CMCase production after optimization). Thus, this newly developed SSF bioreactor has highly potential be used as prototype for larger scale bioreactor design